Elevated Soluble Triggering Receptor Expressed on Myeloid Cells (sTREM)-1 Levels in Maternal Serum during Term and Preterm Labor - Tency, Inge (Public Library of Science, 2013)
BACKGROUND: Infection and inflammation are important mechanisms leading to preterm birth. Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) belongs to a family of cell surface receptors that seems to play an important role in fine-tuning the immune response. It has been demonstrated that sTREM-1 is involved in bacterial infection as well as in non-infectious inflammatory conditions. Few studies have investigated serum sTREM-1 expression during preterm labor. Therefore, the purpose of this study was to assess sTREM-1 concentrations in maternal serum during term and preterm labor. METHODS: This case control study included 176 singleton pregnancies in the following groups: patients in (1) preterm labor, delivered before 34 weeks (PTB) (n = 52); (2) GA matched controls, not in labor, matched for gestational age (GA) with the PTB group (n = 52); (3) at term in labor (n = 40) and (4) at term not in labor (n = 32). sTREM-1 concentrations were determined by enzyme-linked immunoassay. RESULTS: sTREM-1 was detected in all serum samples. Median sTREM-1 concentrations were significantly higher in women with PTB vs. GA matched controls (367 pg/ml, interquartile range (IQR) 304–483 vs. 273 pg/ml, IQR 208–334; P<0.001) and in women at term in labor vs. at term not in labor (300 pg/ml, IQR 239–353 vs. 228 pg/ml, IQR 174–285; P<0.001). Women with PTB had significantly higher levels of sTREM-1 compared to women at term in labor (P = 0.004). Multiple regression analysis, with groups recoded as three key covariates (labor, preterm and rupture of the membranes), showed significantly higher sTREM-1 concentrations for labor (+30%, P<0.001) and preterm (+15%, P = 0.005) after adjusting for educational level, history of PTB and sample age. CONCLUSIONS: sTREM-1 concentrations in maternal serum were elevated during spontaneous term and preterm labor and sTREM-1 levels were significantly higher in preterm labor.